2021
DOI: 10.3390/cells10123594
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Chondroitin Sulfate Reduces Invasiveness of Glioma Cells by Suppressing CD44 and Integrin β1 Expression

Abstract: Chondroitin sulfate (CS) is a major component of the extracellular matrix found to be abnormally accumulated in several types of cancer tissues. Previous studies have indicated that CS synthases and modification enzymes are frequently elevated in human gliomas and are associated with poor prognosis. However, the underlying mechanisms of CS in cancer progression and approaches for interrupting its functions in cancer cells remain largely unexplored. Here, we have found that CS was significantly enriched surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Upregulation of genes encoding CSPGs including versican and CSPG4 was also observed in the GBM microenvironment compared to normal tissues. Other studies, like ours, have shown higher levels of CSPGs in GBM tissues than in normal brains 26, 27 . Also, expression of CSPGs and enzymes involved in chondroitin sulphate polymerization is elevated in the GBM microenvironment and corresponds with high tumor grade and poor survival 2830 .…”
Section: Discussionsupporting
confidence: 69%
“…Upregulation of genes encoding CSPGs including versican and CSPG4 was also observed in the GBM microenvironment compared to normal tissues. Other studies, like ours, have shown higher levels of CSPGs in GBM tissues than in normal brains 26, 27 . Also, expression of CSPGs and enzymes involved in chondroitin sulphate polymerization is elevated in the GBM microenvironment and corresponds with high tumor grade and poor survival 2830 .…”
Section: Discussionsupporting
confidence: 69%
“…The experiment was repeated three times. Meanwhile, many research reported that hyaluronic acid (HA) and chondroitin sulfate (CS) could bind specifically with CD44 receptor 26 , 27 . To examine the uptake of CS/BH NPs was mediated by CD-44 receptors, cells were pretreated with excess free CS (5 mg/mL) or HA (5 mg/mL) for 1 h, respectively, then incubated with CS/BH NPs.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, while research has shown that hyperinsulinemia mediates pathologic angiogenesis through the proliferative actions of the ERK MAPK pathway ( 42 , 43 ), chronically elevated levels of insulin may also trigger the expression of EPDR1 and potentially many others through the endoglin/ALK1/Smad1/5 signaling axis. For instance, chondroitin sulfate synthase 2 ( 44 , 45 ) and prostaglandin F2 receptor-associated protein ( 46 , 47 , 48 ) are two of the top hits ranked higher than EPDR1, whereas others, including osteopontin ( 49 , 50 ) and platelet-derived growth factor receptor beta ( 51 , 52 ), represent promising candidates ranked slightly lower based on several parameters including fold changes over negative control and unique peptide counts identified ( Fig. S3 B ).…”
Section: Discussionmentioning
confidence: 99%